KEARIFAN TRADISIONAL DALAM EKOLOGI FLORA TATANGAR BANJAR - Rissari Yayuk (Balai Bahasa Kalimatan Selatan, 2018)
The problem discusses in this study is traditional wisdom in ecology of flora tatangar Banjar. The problem discusses include what a the example in ecology of flora tatangar Banjar. How does traditional wisdom the ecology of flora of tatangar Banjar. The aim of this study is to describe example in ecology of flora tatangar Banjar and traditional wisdom in ecology of flora tatangar Banjar. This study uses descriptive qualitative approach. Data collection techniques are recording and interviewing. Data analysis is done through interpretation based on ecological theory. Data was collected from January 2018 to March 2018. Data collection areas are Karang Intan and Banjarmasin villages, South Kalimanyan Province. The result describes example in ecology of flora tatangar Banjar and traditional wisdom the ecology of flora tatangar Banjar the using plansts as symbol from the sigh of a condition or situation. The behind, the result gives knowledge about respecting sacred areas, determining fertile and unfertile land, reading the start of a season, maintaining potential natural resouries and pay attention when doing plantation. The conclusion behind this study is teaching us about how to adapt and control nature to be harmonious and prosperous.Keywords: culture, tatangar, Banjar